Gaming Globally
XI, 279 p. 14 illus.
Keywords: Video games are inherently transnational by virtue of industrial, textual, and player practices. The contributors touch upon nations not usually examined by game studies - including the former Czechoslovakia, Turkey, India, and Brazil - and also add new perspectives to the global hubs of China, Singapore, Australia, Japan, and the United States.